Serotyping of Campylobacter jejuni/coli. - Abbott, J D (1980)
Antisera were prepared from strains of Campylobacter jejuni/coli isolated from patients in six outbreaks of enteritis. Bactericidal antibodies, and agglutinating antibodies to heat-labile and heat-stable antigens, were demonstrated. These reactions were used to type a number of strains isolated from patients in each outbreak, and to distinguish 'epidemic' from 'non-epidemic' strains.